FORCED MARRIAGE AS ONE OF THE CRIMES OF SEXUAL VIOLENCE - Setyawan, Vincentius (IBLAM LAW REVIEW, 2023)
Forced marriage is an act that is not just a social problem but has turned into a legal problem. Marriages carried out without the consent of the prospective husband and prospective wife have the potential to cause problems in family life, and even have the potential to cause physical, psychological and sexual violence. The purpose of writing this article is to analyze the importance of regulation on forced marriages to prevent family violence, especially sexual violence. Problems will be studied using normative legal research methods, with a statutory approach. The result of this study is that the presence of criminal law by criminalizing forced marriages is an effort to protect society from problems arising from forced marriages, namely the potential for violence, physical, psychological and sexual violence.